KEJADIAN ANEMIA DAN GANGGUAN SIKLUS HAID PADA REMAJA DI CIANGSANA - NAGRAK - Nirmalasari, Rully Ayu; Surjadi, Lily Marliany; Mario, Mario; Maharani, Laksmi (Jurnal Pengabdian Masyarakat Trimedika, 2025)
Background: Anemia in adolescents is a public health problem in Indonesia.  Based on the 2018 Basic Health Research (Riskesdas) report, Based on the 2018 Basic Health Research (Riskesdas) report, 32% of teenagers aged 15-24 years experienced anemia. The majority of teenagers who experience anemia are in the age range 10 – 18 years. Adolescent girls experiencing ongoing anemia can increase morbidity during pregnancy and childbirth. Level of knowledge, diet, nutritional status and menstrual cycle are factors that are said to influence anemia. Method: This activity was carried out in Desember 2023 and was attended by 30 young women aged 10-19 years in the Nagrak and Ciangsana district. The activity consists of several stages, namely interviews about the menstrual cycle, checking hemoglobin levels, checking nutritional status, and education about body mass index. Results: From this activity, it was found that 53.3% of teenagers had a normal body mass index, 96.7% had a normal waist/hip ratio, 50% of teenagers had irregular menstrual cycles, 80% had dysmenorrhea. Meanwhile, regarding the prevalence of anemia, 50% of adolescent girls have mild anemia and 13.3% have moderate anemia. Conclusion: The prevalence of anemia in adolescent girls in Nagrak and Ciangsana subdistricts is still high (63.3%), as are adolescents who experience irregular menstrual cycles and dysmenorrhea.